Heavy metals contamination: implications for health and food safety - Reyes, Yulieth; Vergara, Inés; Torres, Omar; Díaz-Lagos, Mercedes; González-Jimenez, Edgar Emir (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2016)
Contamination by heavy metals in water resources, soil and air poses one of the most severe problems that compromise food safety and public health at global and local level. In this review, the specific problem of contamination by mercury (Hg), arsenic (As), cadmium (Cd) and lead (Pb) in the environment and food is presented. A description of the sources of contamination, exposure in living beings, accumulation and retention in food and consumer products is carried out. Study cases and results in some countries included Colombia are discussed.